Factors affecting adoption of legume technologies and its impact on income of farmers: The case of Sinana and Ginir Woredas of Bale Zone - Tegegne, Y. (Haramaya University, 2017)
In Ethiopia, low productivity of crops has been one of the significant contributors to food insecurity. Encouraging the rural households’ to use improved agricultural technologies and inputs to increase efficiency of production and productivity are among the important policy measures to address the problem undertaken by the government. The objective of this study was to analyze factors influencing the adoption of improved agricultural technologies (improved seed and fertilizer) and its impact on income of farm households of legume producers in Sinana and Ginir Woredas’ of Bale Zone of Oromiya National Regional State. Primary data were collected from a sample of 210 households selected through stratified sampling techniques. Descriptive statistics and econometric models were used to analyze the data. The logit model for PSM and OLS models were used to analyze the impact of technologies and the factors influencing the adoption of agricultural technologies respectively. The results presented that technology access for improved farm inputs, credit accessibility, wealth status of farm households and education level of household head had a significantly influenced on the adoption level of both improved seed and fertilizer technology. On the contrary, high price of improved technology and family size had negatively affected the adoption level of improved farm inputs. Impact assessment of the marginal effect showed that farmers who had adopted improved technology could enhance their annual total income level by 2.8% and the crop income particularly from grain legume has been increased by 41%. The adoption typology of the farmers can be categorized in to four in relation to their current adoption status as tech-oriented, tech-fledglings, tech-adopters, and tech-dropouts. Based on the findings, the study suggests that strengthening the promotion of full scale technology adoption will have crucial role towards improving the livelihood of households in the study area. In doing so, managing the possible influencing factors that affect adoption of legume technology should be a prerequisite.